Influential factors cultivating Indonesian EFL educators' professional identity construction - Wijaya, Kristian Florensio (Journal of English Language and Pedagogy (JELPA), 2023)
One of the essential underlying premises that need to be kept in mind to maintain Indonesian EFL educators’ professionalism is with the support of the robust establishment of professional identity. Previously-reviewed studies conducted in Indonesian EFL teaching-learning contexts held a strong contention that a higher level of professional identity construction would enable language teachers to show their best educational endeavour to fully fulfill the educational demands. This current small-scale qualitative study was initiated with the support of a library analysis approach to generate more comprehensible and applicable research results. To attain this major study objective, the researcher conducted an in-depth thematic analysis of 20 previously-conducted Indonesian EFL teachers’ professional identity construction studies to yield more orderly research outcomes. Two major-specific factors are believed to cultivate Indonesian EFL educators’ professional identity construction namely: (1) viable motivation to advance an entire educational quality and (2) rigorous external support emanating from educational stakeholders. To this end, it can be fairly inferred that Indonesian EFL educators can fully possess a higher degree of professional identity in an occasion where both internal motivation and mutual external support are embedded within their professional lives.